Crystallographic and Geometry-Optimization Study On 2,4,6-Trinitrophenol:3-Methyl-4-Nitropyridine N-Oxide (1/1) - Mohd. Zain, Sharifuddin; Rodzi Mohammad, Mohd.; Seik Weng, Ng (Malaysian Journal of Science, 2005)
In the crystal structure of 2,4,6-trinitrophenol:3-methyl-4-nitropyridine N-oxide (1/1) (TNP:POM), the hydroxyl group of TNP is hydrogen bonded to the N-oxide oxygen atom of POM [O⋯O = 2.607(5) Å], and adjacent molecules are linked by a supramolecular C-H$_{aromaric}$⋯O$_{N-oxide}$ interaction across a center-of-inversion to form a weakly-held TNP:POM dimer. The ortho-nitro group that engages in hydrogen bonding is nearly coplanar with the aromatic ring of the TNP moiety whereas the ortho-nitro group that is free is severely twisted. Geometry-optimization calculations at B3LYP/6-31G* level was also carried out for comparison.